Strong Force: The Story of Physicist Shirley Ann Jackson - Diane O'Connell (The National Academies Press, 2006)
Shirley Ann Jackson sees the unseen. She's an expert in the invisible particles that make up everything in the universe, including you. Shirley is a theoretical physicist, a scientist who studies the subatomic world using only paper, pencils, computers and the most important tool of all: her imagination. Shirley's passion for science blossomed during her childhood, with bumblebee experiments and go-cart races. But it's her talent for math and her drive to succeed that have taken her career in amazing directions. Shirley uses her knowledge of electrons, neutrinos, and other particles of matter to better the lives of others—from solving important technology problems to teaching college physics to making nuclear power plants safer. A natural-born leader, Shirley has always seized opportunities and broken down racial barriers, not only for herself but for others. Strong Force is the compelling story of an African American scientist and her science. To tell this true story of courage, author Diane O'Connell drew on firsthand accounts from Shirley and her friends, family, and colleagues. How did a young bee collector grow up to be a world-renowned physicist? The life story of Shirley Ann Jackson will intrigue and inspire readers of all ages. This title aligns to Common Core standards: Interest Level Grades 6 - 8; Reading Level Grade level Equivalent: 7.1: Lexile Measure: 1080L; DRA: Not Available; Guided Reading: Z
Keywords: Explore Science; Math, Chemistry, and Physics; Biography and Autobiography

Robust Methods for the Analysis of Images and Videos for Fisheries Stock Assessment: Summary of a Workshop - National Research Council (The National Academies Press, 2015)
The National Marine Fisheries Service (NMFS) is responsible for the stewardship of the nation's living marine resources and their habitat. As part of this charge, NMFS conducts stock assessments of the abundance and composition of fish stocks in several bodies of water. At present, stock assessments rely heavily on human data-gathering and analysis. Automatic means of fish stock assessments are appealing because they offer the potential to improve efficiency and reduce human workload and perhaps develop higher-fidelity measurements. The use of images and video, when accompanies by appropriate statistical analyses of the inferred data, is of increasing importance for estimating the abundance of species and their age distributions. Robust Methods for the Analysis of Images and Videos for Fisheries Stock Assessment is the summary of a workshop convened by the National Research Council Committee on Applied and Theoretical Statistics to discuss analysis techniques for images and videos for fisheries stock assessment. Experts from diverse communities shared perspective about the most efficient path toward improved automation of visual information and discussed both near-term and long-term goals that can be achieved through research and development efforts. This report is a record of the presentations and discussions of this event.
Keywords: Math, Chemistry, and Physics; Agriculture; Surveys and Statistics

The Use and Storage of Methyl Isocyanate (MIC) at Bayer CropScience - National Research Council (The National Academies Press, 2012)
The use of hazardous chemicals such as methyl isocyanate can be a significant concern to the residents of communities adjacent to chemical facilities, but is often an integral part of the chemical manufacturing process. In order to ensure that chemical manufacturing takes place in a manner that is safe for workers, members of the local community, and the environment, the philosophy of inherently safer processing can be used to identify opportunities to eliminate or reduce the hazards associated with chemical processing. However, the concepts of inherently safer process analysis have not yet been adopted in all chemical manufacturing plants. The Use and Storage of Methyl Isocyanate (MIC) at Bayer CropScience presents a possible framework to help plant managers choose between alternative processing options-considering factors such as environmental impact and product yield as well as safety- to develop a chemical manufacturing system. In 2008, an explosion at the Bayer CropScience chemical production plant in Institute, West Virginia, resulted in the deaths of two employees, a fire within the production unit, and extensive damage to nearby structures. The accident drew renewed attention to the fact that the Bayer facility manufactured and stores methyl isocyanate, or MIC - a volatile, highly toxic chemical used in the production of carbamate pesticides and the agent responsible for thousands of death in Bhopal, India, in 1984. In the Institute accident, debris from the blast hit the shield surrounding a MIC storage tank, and although the container was not damaged, an investigation by the U.S. Chemical Safety and Hazard Investigation Board found that the debris could have struck a relief valve vent pipe and cause the release of MIC to the atmosphere. The Board's investigation also highlighted a number of weaknesses in the Bayer facility's emergency response systems. In light of these concerns, the Board requested the National Research Council convene a committee of independent experts to write a report that examines the use and storage of MIC at the Bayer facility. The Use and Storage of Methyl Isocyanate (MIC) at Bayer CropScience also evaluates the analyses on alternative production methods for MIC and carbamate pesticides preformed by Bayer and the previous owners of the facility.
Keywords: Math, Chemistry, and Physics

Manipulating Quantum Systems: An Assessment of Atomic, Molecular, and Optical Physics in the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The field of atomic, molecular, and optical (AMO) science underpins many technologies and continues to progress at an exciting pace for both scientific discoveries and technological innovations. AMO physics studies the fundamental building blocks of functioning matter to help advance the understanding of the universe. It is a foundational discipline within the physical sciences, relating to atoms and their constituents, to molecules, and to light at the quantum level. AMO physics combines fundamental research with practical application, coupling fundamental scientific discovery to rapidly evolving technological advances, innovation and commercialization. Due to the wide-reaching intellectual, societal, and economical impact of AMO, it is important to review recent advances and future opportunities in AMO physics. Manipulating Quantum Systems: An Assessment of Atomic, Molecular, and Optical Physics in the United States assesses opportunities in AMO science and technology over the coming decade. Key topics in this report include tools made of light; emerging phenomena from few- to many-body systems; the foundations of quantum information science and technologies; quantum dynamics in the time and frequency domains; precision and the nature of the universe, and the broader impact of AMO science.
Keywords: Math, Chemistry, and Physics

Burning Plasma: Bringing a Star to Earth - National Research Council (The National Academies Press, 2004)
Significant advances have been made in fusion science, and a point has been reached when we need to decide if the United States is ready to begin a burning plasma experiment. A burning plasma—in which at least 50 percent of the energy to drive the fusion reaction is generated internally—is an essential step to reach the goal of fusion power generation. The Burning Plasma Assessment Committee was formed to provide advice on this decision. The committee concluded that there is high confidence in the readiness to proceed with the burning plasma step. The International Thermonuclear Experimental Reactor (ITER), with the United States as a significant partner, was the best choice. Once a commitment to ITER is made, fulfilling it should become the highest priority of the U.S. fusion research program. A funding trajectory is required that both captures the benefits of joining ITER and retains a strong scientific focus on the long-range goals of the program. Addition of the ITER project will require that the content, scope, and level of U.S. fusion activity be defined by program balancing through a priority-setting process initiated by the Office of Fusion Energy Science.
Keywords: Math, Chemistry, and Physics; Space and Aeronautics

Controlling the Quantum World: The Science of Atoms, Molecules, and Photons - National Research Council (The National Academies Press, 2007)
As part of the Physics 2010 decadal survey project, the Department of Energy and the National Science Foundation requested that the National Research Council assess the opportunities, over roughly the next decade, in atomic, molecular, and optical (AMO) science and technology. In particular, the National Research Council was asked to cover the state of AMO science, emphasizing recent accomplishments and identifying new and compelling scientific questions. Controlling the Quantum World, discusses both the roles and challenges for AMO science in instrumentation; scientific research near absolute zero; development of extremely intense x-ray and laser sources; exploration and control of molecular processes; photonics at the nanoscale level; and development of quantum information technology. This book also offers an assessment of and recommendations about critical issues concerning maintaining U.S. leadership in AMO science and technology.
Keywords: Math, Chemistry, and Physics; Conflict and Security Issues

Atoms, Molecules, and Light: AMO Science Enabling the Future - National Research Council (The National Academies Press, 2002)
With the publication in 1994 of Atomic, Molecular, and Optical Science: An Investment in the Future (the FAMOS report), the National Research Council launched the series Physics in a New Era, its latest survey of physics. Each of the six area volumes in the survey focuses on a different subfield of physics, describing advances since the last decadal survey and suggesting future opportunities and directions. This survey culminated in 2001 with the publication of the seventh and final volume, Physics in a New Era: An Overview. Since the publication of the FAMOS report, the developments in atomic, molecular, and optical (AMO) science have been amazing. Significant advances in areas such as cooling and trapping, atom and quantum optics, single-atom and single-molecule detection, and ultrafast and ultra intense phenomena, along with the emergence of new applications, made it clear that an update of the FAMOS report was needed. With support from the National Science Foundation and the Department of Energy, the Committee for an Updated Assessment of Atomic, Molecular, and Optical Science was formed. The committee's statement of task reads as follows: The committee will prepare a narrative document that portrays the advances in AMO science and its impact on society. This report highlights selected forefront areas of AMO science, emphasizing recent accomplishments and new opportunities, identifies connections between AMO science and other scientific fields, emerging technologies, and national needs, describes career opportunities for AMO scientists. To accomplish its task and at the same time reach a broad audience, the committee decided to present its report in the form of a brochure highlighting selected advances, connections, and impacts on national needs. An exhaustive assessment of the field, which will fall within the purview of the next decadal survey, was not the goal of the update. The committee would like to express its gratitude for the informative interactions it had with many scientists and policy makers. Many colleagues completed a questionnaire and suggested topics to be included in this report. The final selection of topics was made in accordance with the criteria set forth in the statement of task. While this report was still being written, the tragic events of September 11, 2001, occurred. AMO science and its applications have already played and will continue to play a central role in our nation's response to terrorist threats from conventional as well as chemical or biological weapons. Some of the technology discussed in this report in the chapter "AMO Science Enhancing National Defense" was used successfully for the U.S. military response in Afghanistan—the Global Positioning System (GPS) and laser-guided munitions are just two examples. AMO science will also enable the development of early detection techniques that will help to neutralize the threat from biological and chemical agents.
Keywords: Math, Chemistry, and Physics; Conflict and Security Issues

Catalysis for Energy: Fundamental Science and Long-Term Impacts of the U.S. Department of Energy Basic Energy Sciences Catalysis Science Program - National Research Council (The National Academies Press, 2009)
This book presents an in-depth analysis of the investment in catalysis basic research by the U.S. Department of Energy (DOE) Office of Basic Energy Sciences (BES) Catalysis Science Program. Catalysis is essential to our ability to control chemical reactions, including those involved in energy transformations. Catalysis is therefore integral to current and future energy solutions, such as the environmentally benign use of hydrocarbons and new energy sources (such as biomass and solar energy) and new efficient energy systems (such as fuel cells). Catalysis for Energy concludes that BES has done well with its investment in catalysis basic research. Its investment has led to a greater understanding of the fundamental catalytic processes that underlie energy applications, and it has contributed to meeting long-term national energy goals by focusing research on catalytic processes that reduce energy consumption or use alternative energy sources. In some areas the impact of the research has been dramatic, while in others, important advances in catalysis science are yet to be made.
Keywords: Energy and Energy Conservation; Math, Chemistry, and Physics

Atomic, Molecular, and Optical Science: An Investment in the Future - National Research Council (The National Academies Press, 1994)
This book responds to the call for a clear description of the role of basic science in meeting societal needs. It gives examples of societal benefits of atomic, molecular, and optical (AMO) science in a number of key areas, including industrial technology, information technology, energy, global change, defense, health and medical technology, space technology, and transportation. This volume highlights the role of lasers in trapping, cooling, and manipulating individual atoms and molecules to make possible ultraprecise atomic clocks, structural engineering at the atomic level (nanotechnology), and new approaches to the study of deoxyribonucleic acid (DNA). AMO science is shown to be a field that is both an intellectually important basic science and a powerful enabling science that supports many other areas of science and technology.
Keywords: Math, Chemistry, and Physics

Symposium on Microseisms: Held at Arden House, Harriman, N.Y. 4-6 September 1952, Sponsored by the Office of Naval Research, and the Geophysical Research Directorate of the U.S. Air Force. - National Research Council (The National Academies Press, 1953)
Keywords: Math, Chemistry, and Physics

Chemical Structure Information Handling: A Review of the Literature, 1962-1968 (The National Academies Press, 1969)
Keywords: Math, Chemistry, and Physics

Nuclear Physics: Exploring the Heart of Matter - National Research Council (The National Academies Press, 2013)
The principal goals of the study were to articulate the scientific rationale and objectives of the field and then to take a long-term strategic view of U.S. nuclear science in the global context for setting future directions for the field. Nuclear Physics: Exploring the Heart of Matter provides a long-term assessment of an outlook for nuclear physics. The first phase of the report articulates the scientific rationale and objectives of the field, while the second phase provides a global context for the field and its long-term priorities and proposes a framework for progress through 2020 and beyond. In the second phase of the study, also developing a framework for progress through 2020 and beyond, the committee carefully considered the balance between universities and government facilities in terms of research and workforce development and the role of international collaborations in leveraging future investments. Nuclear physics today is a diverse field, encompassing research that spans dimensions from a tiny fraction of the volume of the individual particles (neutrons and protons) in the atomic nucleus to the enormous scales of astrophysical objects in the cosmos. Nuclear Physics: Exploring the Heart of Matter explains the research objectives, which include the desire not only to better understand the nature of matter interacting at the nuclear level, but also to describe the state of the universe that existed at the big bang. This report explains how the universe can now be studied in the most advanced colliding-beam accelerators, where strong forces are the dominant interactions, as well as the nature of neutrinos.
Keywords: Math, Chemistry, and Physics

Final Report of the Committee on a Strategic Plan for U.S. Burning Plasma Research - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Fusion offers the prospect of virtually unlimited energy. The United States and many nations around the world have made enormous progress toward achieving fusion energy. With ITER scheduled to go online within a decade and demonstrate controlled fusion ten years later, now is the right time for the United States to develop plans to benefit from its investment in burning plasma research and take steps to develop fusion electricity for the nation's future energy needs. At the request of the Department of Energy, the National Academies of Sciences, Engineering, and Medicine organized a committee to develop a strategic plan for U.S. fusion research. The final report's two main recommendations are: (1) The United States should remain an ITER partner as the most cost-effective way to gain experience with a burning plasma at the scale of a power plant. (2) The United States should start a national program of accompanying research and technology leading to the construction of a compact pilot plant that produces electricity from fusion at the lowest possible capital cost.
Keywords: Math, Chemistry, and Physics

Ion Storage Rings for Atomic Physics Research (The National Academies Press, 1988)
Keywords: Math, Chemistry, and Physics; Surveys and Statistics

High Magnetic Field Science and Its Application in the United States: Current Status and Future Directions - National Research Council (The National Academies Press, 2013)
The Committee to Assess the Current Status and Future Direction of High Magnetic Field Science in the United States was convened by the National Research Council in response to a request by the National Science Foundation. This report answers three questions: (1) What is the current state of high-field magnet science, engineering, and technology in the United States, and are there any conspicuous needs to be addressed? (2) What are the current science drivers and which scientific opportunities and challenges can be anticipated over the next ten years? (3) What are the principal existing and planned high magnetic field facilities outside of the United States, what roles have U.S. high field magnet development efforts played in developing those facilities, and what potentials exist for further international collaboration in this area? A magnetic field is produced by an electrical current in a metal coil. This current exerts an expansive force on the coil, and a magnetic field is "high" if it challenges the strength and current-carrying capacity of the materials that create the field. Although lower magnetic fields can be achieved using commercially available magnets, research in the highest achievable fields has been, and will continue to be, most often performed in large research centers that possess the materials and systems know-how for forefront research. Only a few high field centers exist around the world; in the United States, the principal center is the National High Magnetic Field Laboratory (NHMFL). High Magnetic Field Science and Its Application in the United States considers continued support for a centralized high-field facility such as NHFML to be the highest priority. This report contains a recommendation for the funding and siting of several new high field nuclear magnetic resonance magnets at user facilities in different regions of the United States. Continued advancement in high-magnetic field science requires substantial investments in magnets with enhanced capabilities. High Magnetic Field Science and Its Application in the United States contains recommendations for the further development of all-superconducting, hybrid, and higher field pulsed magnets that meet ambitious but achievable goals.
Keywords: Math, Chemistry, and Physics

Advancing Chemistry and Quantum Information Science: An Assessment of Research Opportunities at the Interface of Chemistry and Quantum Information Science in the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The field of quantum information science (QIS) has witnessed a dramatic rise in scientific research activities in the 21st century as excitement has grown about its potential to revolutionize communications and computing, strengthen encryption, and enhance quantum sensing, among other applications. While, historically, QIS research has been dominated by the field of physics and computer engineering, this report explores how chemistry - in particular the use of molecular qubits - could advance QIS. In turn, researchers are also examining how QIS could be used to solve problems in chemistry, for example, to facilitate new drug and material designs, health and environmental monitoring tools, and more sustainable energy production. Recognizing that QIS could be a disruptive technology with the potential to create groundbreaking products and new industries, Advancing Chemistry and Quantum Information Science calls for U.S. leadership to build a robust enterprise to facilitate and support research at the intersection of chemistry and QIS. This report identifies three key research areas: design and synthesis of molecular qubit systems, measurement and control of molecular quantum systems, and experimental and computational approaches for scaling qubit design and function. Advancing Chemistry and Quantum Information Science recommends that the Department of Energy, National Science Foundation, and other funding agencies should support multidisciplinary and collaborative research in QIS, the development of new instrumentation, and facilities, centralized and open-access databases, and efforts to create a more diverse and inclusive chemical workforce.
Keywords: Math, Chemistry, and Physics

Reducing the Time from Basic Research to Innovation in the Chemical Sciences: A Workshop Report to the Chemical Sciences Roundtable - National Research Council (The National Academies Press, 2003)
Innovation, the process by which fundamental research becomes a commercial product, is increasingly important in the chemical sciences and is changing the nature of research and development efforts in the United States. The workshop was held in response to requests to speed the R&D process and to rapidly evolve the patterns of interaction among industry, academe, and national laboratories. The report contains the authors' written version of the workshop presentations along with audience reaction.
Keywords: Math, Chemistry, and Physics

Plasma Science: Enabling Technology, Sustainability, Security, and Exploration - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Plasma Science and Engineering transforms fundamental scientific research into powerful societal applications, from materials processing and healthcare to forecasting space weather. Plasma Science: Enabling Technology, Sustainability, Security and Exploration discusses the importance of plasma research, identifies important grand challenges for the next decade, and makes recommendations on funding and workforce. This publication will help federal agencies, policymakers, and academic leadership understand the importance of plasma research and make informed decisions about plasma science funding, workforce, and research directions.
Keywords: Math, Chemistry, and Physics; Space and Aeronautics

Nuclear Physics: The Core of Matter, The Fuel of Stars - National Research Council (The National Academies Press, 1999)
Dramatic progress has been made in all branches of physics since the National Research Council's 1986 decadal survey of the field. The Physics in a New Era series explores these advances and looks ahead to future goals. The series includes assessments of the major subfields and reports on several smaller subfields, and preparation has begun on an overview volume on the unity of physics, its relationships to other fields, and its contributions to national needs. Nuclear Physics is the latest volume of the series. The book describes current activity in understanding nuclear structure and symmetries, the behavior of matter at extreme densities, the role of nuclear physics in astrophysics and cosmology, and the instrumentation and facilities used by the field. It makes recommendations on the resources needed for experimental and theoretical advances in the coming decade.
Keywords: Math, Chemistry, and Physics; Space and Aeronautics

Radiochemistry of Mercury - National Research Council (The National Academies Press, 1970)